The role of social media in expanding vocabulary, Coronavirus pandemic for example - Barzan Jaafar Ali (Zanco Journal of Humanity Sciences)
Since we live in an era where technology plays a crucial role in human being’s everyday life, it has become the voice of society. Thus, media can be described as a reflection of the society, which make communication among people around the world easier as well as helps in making people informed with the latest news and what is happening around us. While a few decades ago, to send a message to someone, we had to wait for days to deliver the message, now any conversation or anything important can be sent or occurred in a second. Accordingly, social media as one of the foremost platforms for communication has brought the world together on one single platform. Based on these, social media has also helped the language to develop swiftly as when a new vocabulary comes out, we do not need to wait until it will be added to the dictionary but through media we will be informed or/and will learn the word. Hence, the research study intentions to explore the role of social media in developing vocabulary and how Coronavirus has helped to introduce a wave of new vocabulary and phrases among English non-native speakers. The sample chosen for the study consists of 40 English non-native speakers: 20 females and 20 males, ranging in age from 18-30 years. To achieve the target objective of this study, a questionnaire has been selected. The findings show that social media has been a great source of information especially in term of new vocabulary and vocabulary developments. Moreover, COVID-19 has caused to create a new range of phrases and words. In addition, the findings show that how social media and social crises play a crucial role in lexical innovation and creativity.